The K2 Galactic Archaeology Program: Overview, target selection, and survey properties. Issue 2 (22nd July 2022) - Sharma, Sanjib; Stello, Dennis; Zinn, Joel C; Reyes, Claudia; Hon, Marc; Bland-Hawthorn, Joss
ABSTRACT: K2 was a community-driven NASA mission where all targets were proposed through guest observer programmes. Here we provide an overview of one of the largest of these endeavours, the K2 Galactic Archaeology Programme (K2GAP), with about 25 per cent of the observed targets being allocated to this programme. K2GAP provides asteroseismic parameters for about 23 000 giant stars across the Galaxy, which together with spectroscopic stellar parameters can give age and masses of stars. We discuss in detail the target selection procedure and provide a python program that implements the selection function (github.com/sanjibs/k2gap ). Broadly speaking, the targets were selected on 2MASS colour J − Ks > 0.5, with finely tuned adjustments for each campaign. We discuss the detection completeness of the asteroseismic parameters νmax and Δν. About 14 per cent of giants were found to miss νmax detections and it was difficult to detect Δν for RC stars. Making use of the selection function, we compare the observed distribution of asteroseismic masses to theoretical predictions. The median asteroseismic mass is higher by about 4 per cent compared to predictions. We provide a selection-function-matched mock catalogue of stars based on a synthetic model of the Galaxy for the community to use in subsequent analyses of the K2GAP data set (physics.usyd.edu.au/k2gap/download/ ).